2022
DOI: 10.1093/dote/doac011
|View full text |Cite
|
Sign up to set email alerts
|

McKeown esophagectomy: robot-assisted versus conventional minimally invasive technique—systematic review and meta-analysis

Abstract: Background and purpose: This meta-analysis assesses the surgical outcomes between robot-assisted minimally-invasive McKeown esophagectomy and conventional one. Method: This meta-analysis searched the Web of Science, PUBMED, and EMBASE from the database’s inception to January 2022. Altogether, 1073 records were identified in the literature search. Studies that evaluated the outcomes between robot-assisted minimally-invasive McKeown esophagectomy and conventional one among postoperative patients with oesophageal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 47 publications
5
10
0
Order By: Relevance
“…With regard to the comparison of postoperative complications in the two groups, our results indicated that RAMIE has similar outcomes to MIE, but is associated with a lower incidence of pneumonia [9.61% (95% CI: 7.38%–11.84%) vs 14.74% (95% CI: 11.62%–18.15%); OR = 0.73; 95% CI: 0.58-0.93; P =0.01]. This result was in line with several recently published studies 58–60. This benefit could be attributed to the better visual field and more precise identification of structures with the assistance of a robot system, improving the preservation of the pulmonary parenchyma and nerves, especially the pulmonary branches of the vagus nerve 61.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…With regard to the comparison of postoperative complications in the two groups, our results indicated that RAMIE has similar outcomes to MIE, but is associated with a lower incidence of pneumonia [9.61% (95% CI: 7.38%–11.84%) vs 14.74% (95% CI: 11.62%–18.15%); OR = 0.73; 95% CI: 0.58-0.93; P =0.01]. This result was in line with several recently published studies 58–60. This benefit could be attributed to the better visual field and more precise identification of structures with the assistance of a robot system, improving the preservation of the pulmonary parenchyma and nerves, especially the pulmonary branches of the vagus nerve 61.…”
Section: Discussionsupporting
confidence: 89%
“…This result was in line with several recently published studies. [58][59][60] This benefit could be attributed to the better visual field and more precise identification of structures with the assistance of a robot system, improving the preservation of the pulmonary parenchyma and nerves, especially the pulmonary branches of the vagus nerve. 61 The well-reserved structure of the vagus nerve regulates many important pulmonary functions, including cough reflex, mucous production, and bronchus diameter, which restrain the presence of pneumonia and accelerate postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Both abdominal and mediastinal lymph node dissection seem to be superior after RAMIE, being more beneficial in the lymphadenectomy across the right laryngeal nerve [ 44 ]. Overall, what is clear among most of the reviews, including the present study, is that the intraoperative, perioperative, and overall clinical outcomes following MIE and RAMIE in high-volume centers are better compared with the open approach, whereas the long-term postoperative results of both MIE and RAMIE are at least equivalent [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review and meta-analysis directly compares relevant short-term outcomes between robot-assisted and conventional minimally invasive esophagectomies in esophageal cancer patients. Previous meta-analysis [ 17 24 ] concluded that RAMIE is a superior surgical approach when compared to cMIE regarding blood loss, number of harvested lymph nodes, RLN palsy and pulmonary complications, while operating time is shorter in cMIE. Nonetheless, some of these results are also associated with a high percentage of heterogeneity among the studies, compromising their validity.…”
Section: Discussionmentioning
confidence: 99%
“…RAMIE was associated with a tendency of longer operating time, less estimated blood loss and shorter length of hospital stay. RAMIE also yielded a larger number of lymph nodes and had lower rates of pulmonary complications when compared to cMIE [ 17 24 ].…”
Section: Introductionmentioning
confidence: 99%